2020
DOI: 10.1097/adm.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transition From Methadone to Buprenorphine Utilizing a Micro-dosing Protocol in the Outpatient Veteran Affairs Setting

Abstract: Objectives: Alternative transition protocols from methadone to buprenorphine in the treatment of opioid use disorder (OUD) are needed to reduce the risk of precipitated withdrawal and opioid use during induction. Methods: Case report (n = 1). Results: One patient with OUD underwent a rapid microinduction outpatient protocol that did not cause precipitated withdrawal or require preceding taper before cessatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…3 Case reports describe alternative approaches utilizing small, frequent doses of buprenorphine-naloxone to avoid withdrawal symptoms, and rapidly transition patients off full agonist opioids. [4][5][6][7][8][9][10][11][12][13] None of these case studies include adolescents or individuals with SCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Case reports describe alternative approaches utilizing small, frequent doses of buprenorphine-naloxone to avoid withdrawal symptoms, and rapidly transition patients off full agonist opioids. [4][5][6][7][8][9][10][11][12][13] None of these case studies include adolescents or individuals with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, induction of buprenorphine in opioid‐dependent individuals required mild to moderate opioid withdrawal and cessation of full opioid agonists for 24‐48 h in a clinical setting 3 . Case reports describe alternative approaches utilizing small, frequent doses of buprenorphine‐naloxone to avoid withdrawal symptoms, and rapidly transition patients off full agonist opioids 4–13 . None of these case studies include adolescents or individuals with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…From the available data, patients were successfully transitioned from a variety of full opioid agonists over a wide range of dosing, including hydromorphone, heroin, methadone, diacetylmorphine and methadone, oxycodone, and methadone, largely without significant withdrawal symptoms. Six studies have also demonstrated the use of transdermal fentanyl or buprenorphine patches as viable bridging treatments to eliminate withdrawal symptoms during the transition to buprenorphine 15,22‐24,27,32 . While not all authors measured or documented the COWS score for their participants, of those available, the average COWS score seldom registered within even the mild severity category.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The patient received his usual dose of methadone throughout the induction and was transitioned to SL buprenorphine using the transdermal buprenorphine patch for the first 3 days. Methadone was discontinued on the 11th day 27 …”
Section: Description Of Studiesmentioning
confidence: 99%
“…2 Case reports describe alternative approaches utilizing small, frequent doses of buprenorphinenaloxone to avoid withdrawal symptoms and rapidly transition patients off full agonist opioids. [3][4][5][6][7][8][9][10][11][12] None of these case studies include adolescents or individuals with SCD.…”
Section: Introductionmentioning
confidence: 99%